2011
DOI: 10.1007/s00439-010-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide screen of gene–gene interactions for rheumatoid arthritis susceptibility

Abstract: The objective of the study was to identify interacting genes contributing to rheumatoid arthritis (RA) susceptibility and identify SNPs that discriminate between RA patients who were anti-cyclic citrullinated protein positive and healthy controls. We analyzed two independent cohorts from the North American Rheumatoid Arthritis Consortium. A cohort of 908 RA cases and 1,260 controls was used to discover pairwise interactions among SNPs and to identify a set of single nucleotide polymorphisms (SNPs) that predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…In the application of RFs to genome-wide association data, the focus has been on different features of the algorithm. Whereas some used RFs to identify candidate regions similar to standard analyses [31], others focused on the detection of gene-gene interactions [46]. In a third group of applications, the resulting genetic regions are not of interest in themselves; instead, a prediction model is built using hundreds of SNPs at a time [19].…”
Section: Rf Applications In Bioinformatics: Some Examplesmentioning
confidence: 99%
“…In the application of RFs to genome-wide association data, the focus has been on different features of the algorithm. Whereas some used RFs to identify candidate regions similar to standard analyses [31], others focused on the detection of gene-gene interactions [46]. In a third group of applications, the resulting genetic regions are not of interest in themselves; instead, a prediction model is built using hundreds of SNPs at a time [19].…”
Section: Rf Applications In Bioinformatics: Some Examplesmentioning
confidence: 99%
“…The method of RF used by Liu et al [36] is to identify rheumatoid arthritis (RA) susceptibility by contributed gene-gene interactions and to identify SNPs which can distinguish who were anticyclic citrullinated protein positive and healthy controls among RA patients. The result showed that RF had distinguish RA cases from controls with 70% accuracy when applied to a set of SNPs selected from single-SNP and pairwise interaction tests identified 93 SNPs.…”
Section: Random Forestmentioning
confidence: 99%
“…For example, SVM, random forest, and neural network methods have been used to identify SNP combinations that are associated with type 2 diabetes [2], childhood allergic asthma [28], rheumatoid arthritis [17], and other diseases [24]. However, these methods need to focus on a small set of candidate SNPs, often on candidate disease genes, in order to identify SNP combinations for targeted diseases or phenotypes.…”
Section: Introductionmentioning
confidence: 99%